KEMISKINAN dan KESEJAHTERAAN - Idzaa Marfuah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2000)
Poverty is a vicious circle problem, which is very hard to separate its causes and effects. Vulnerable economic foundation, bureaucratic corrupted and undemocratic government has caused economic crisis become an apprehensive moral crisis. To overcome this problem, sustainable integration of the society and government will have to be exist and finally the nation wealth will be achieved